Anterior cruciate ligament reconstruction using a hamstring tendon graft between 2020-2023 - يوسف, علي (Latakia University Journal -Medical Sciences Series, 2024)
Objectives : To study the results of anterior cruciate ligament (ACL) prosthetics using a tendon graft and their impact on the rehabilitation period Materials and Methods: This study included 22 patients from the reviewers of Tishreen University Hospital in Lattakia between the year of 2020-2023. All the patients in the study underwent anterior cruciate ligament (ACL) reconstruction using Hamstring tendon graft after clinical examination and appropriate radiographic investigations were performed . Rehabilitation was recommended for all patients after surgery and cases were followed up at intervals and clinical and functional reassessments of those affected . Results: The sample consisted of 22 patients, with a predominance of males by 90.9%, the majority of patients were within the age group between 19 – 25 years 40.9%. Based on the results of clinical examination and evaluation of the results of radiological tests, including MRI, chronic injuries accounted for the most common cases in our study by almost 82% . ACL injuries are associated with damage to various structures in the knee joint,where MCF injuries accounted for the majority of cases by 68%. The patients were followed up after the surgical procedure with ( ACL ) reconstruction using the hamstring tendon graft via laparoscopic surgery during the rehabilitation period in two stages (after 6 months, then a year) after surgery . The VAS and IKDC criteria were used in the functional assessment of the knee joint with the investigation of the presence of pain and the results were positive, as our study recorded the absence of pain one year after the injury of 63.6% of all patients . The study also found that there was a noticeable improvement in knee function according to the IKDC assessment, where the results were excellent in 18% of patients after 6 months of surgery, but the percentage increased significantly to reach 54.5% a year after surgery. Conclusion: This study showed the positive results of the arthroscopic treatment of ACL rupture using Hamstring tendon graft , which proves the role of arthroscopic surgery and the importance of the previous surgical technique in the management of such cases .